Religious circumcision on the NHS: opinions of Pakistani people in Middlesbrough, England - Bhopal, Raj; Madhok, R; Hameed, A (My University, 1998)
Pakistanis represent the third largest ethnic minority group in the UK and their major religion--Islam--advocates male circumcision. Interviews with 63 men and 63 women of Pakistani origin, living in Middlesbrough, England, in 1991, explored attitudes toward religious circumcision provided through the National Health Service (NHS). In Middlesbrough, the local health authority does not purchase services for nonmedical circumcision. Overall, 53 respondents (67%) considered it very important that the NHS cover circumcision, 30 (37%) regarded it as important, 6 (7%) thought it was not very important or not important, and 12 (15%) had no opinion. Men were more likely than women to consider this very important or important (60% and 44%, respectively). These findings indicate that the provision of circumcision services by the NHS is important to those most affected and should be given further consideration.
Keywords: ethnicity